Efektivitas Penerapan Zakat Online Terhadap Peningkatan Pembayaran Zakat Pada Lembaga DT Peduli - Ella Fadilla Damanik; Marliyah Marliyah (Jurnal Kajian dan Penelitian Umum, 2023)
Zakat has a very strong sanctity and humanitarian dimension. In the humanitarian dimension, zakat plays an important role in ensuring wealth distribution to create equitable welfare. The problem is that the implementation, especially in collecting zakat from people who are obliged to pay zakat, has not been realized properly. DT Peduli, one of the National Amil Zakat Institutions, runs an online zakat collection system in line with the increasing advancement of internet technology. This article is a research to determine the effectiveness of DT Peduli's online zakat system in collecting zakat from muzakki. The results of this study show that the online zakat collection exceeded the 2% planned target. The 2017 zakat collection in DT Peduli targeted Rp. 1, 114, 329. 320 and the amount achieved was Rp. 1, 242. 957. 097. Therefore, the implementation of DT Peduli's financial technology-based zakat payment system can be effectively implemented.